Design and Test on Simulating Test-bed of Refrigerated Transportation Condition - Xie Ruhe; Liu Guanghai; Guo Cheng (Zhileng xuebao)
A simulating test- bed of refrigerated transportation condition was designed and constructed. The test- bed consists two parts. The first part is a simulating unit of exterior environment, which could simulate temperature condition , humidity condition , and velocity condition by controlling the machine. Moreover, these parameters could be adjusted and assembled discretionarily. The second part is a simulating unit of refrigerated transportation container. The place and size of its entrance and exit could be adjusted, the direction and quantity of the wind can be changed discretionarily in this unit, and temperature, humidity and atmosphere component could be assembled and adjusted.